A new species of the genus Kodaianellissus Wang, Bourgoin & Zhang (Hemiptera: Issidae) with morphological and molecular data - Sohail, Kamran; Huang, Weijian; Zhang, Yalin (Zootaxa, 2020)
Kodaianellissus gibbusis sp. nov. is described from Rawlakot, Azad Jammu & Kashmir (Pakistan), which is first record of the genus Kodaianellissus Wang, Bourgoin & Zhang, 2017 from the country. Morphological characters including male genitalia structure are described and illustrated. A checklist and key to all species of Kodaianellissus are provided. A molecular analysis with morphological characters indicates its placement into the Kodaianellissus.